Stellar feedback in a clumpy galaxy at z ∼ 3.4. Issue 3 (23rd August 2021) - Iani, E; Zanella, A; Vernet, J; Richard, J; Gronke, M; Harrison, C M; Arrigoni-Battaia, F; Rodighiero, G; Burkert, A; Behrendt, M; Chen, Chian-Chou; Emsellem, E; et al.
ABSTRACT: Giant star-forming regions (clumps) are widespread features of galaxies at z ≈ 1−4. Theory predicts that they can play a crucial role in galaxy evolution, if they survive to stellar feedback for >50 Myr. Numerical simulations show that clumps' survival depends on the stellar feedback recipes that are adopted. Up to date, observational constraints on both clumps' outflows strength and gas removal time-scale are still uncertain. In this context, we study a line-emitting galaxy at redshift z ≃ 3.4 lensed by the foreground galaxy cluster Abell 2895. Four compact clumps with sizes ≲280 pc and representative of the low-mass end of clumps' mass distribution (stellar masses ≲2 × 10 8 M⊙ ) dominate the galaxy morphology. The clumps are likely forming stars in a starbursting mode and have a young stellar population (∼10 Myr). The properties of the Lyman- α (Ly α ) emission and nebular far-ultraviolet absorption lines indicate the presence of ejected material with global outflowing velocities of ∼200–300 km s −1 . Assuming that the detected outflows are the consequence of star formation feedback, we infer an average mass loading factor (η) for the clumps of ∼1.8–2.4 consistent with results obtained from hydrodynamical simulations of clumpy galaxies that assume relatively strong stellar feedback. Assuming no gas inflows (semiclosed box model), the estimates of η suggest that the time-scale over which the outflows expel the molecular gas reservoir (≃7 × 10 8 M⊙ ) of the four detected low-mass clumps is ≲50 Myr.